Microstructure and performances for 15-5 PH stainless steel fabricated through the wire-arc additive manufacturing technology. (6th December 2021) - Guo, Chun; Hu, Ruizhang; Chen, Feng
ABSTRACT: In this study, we prepared the 15-5 PH stainless steel samples using the wire-arc additive manufacturing (WAAM) technique. The performances for as-welded samples and samples after post-weld heat treatment (1050°C×1 h) was studied systematically. The main phases are martensite and grain boundary precipitates. There are many dislocations in the crystal structure of the as-welded samples. The Cu phase and Nb phase precipitate, and the number of dislocations in the post-weld heat-treated samples decrease. The microhardness is even in the sample transverse and longitudinal sections, with mean values for the as-welded sample of349.5 HV0.2 and 345.5 HV0.2, respectively, and for the heat-treated sample of 349.7 HV0.2 and 349.2 HV0.2, respectively. The yield strength of the as-welded sample is 666 MPa, the tensile strength is 1080 MPa. The yield strength of the heat-treated sample is 611 MPa, the tensile strength is 1105 MPa.